Estrutura do custo de produção de sementes de trigo: estudo do caso da empresa Kesoja Sementes - Granella, Leandro Munaretto (2011)
Each company in the field of seed production, within its own peculiarities, has a final cost to deliver its customer a product of quality. The objective of the current work was to analyze and discuss the fundamentals of how the items that, make up the final cost of the seed product of KESOJA SEED. It s important for the company, not only from the profitability aspect, but, mainly, the management of the analysis of the weight of these items. The components of fixed costs were appraised, taking as most relevant aspects, machinery depreciation, facilities improvements, followed by fixed labor costs. Considering variable costs and sales expenses, eighteen items in the total were evaluated. Besides the cost of raw material which is responsible for 70% of the final product sale, Royalties, also, had significant impact, reaching 10% and energy costs, technical responsibility , bagging and unrecoverable breake had an impact of 3% each, in the final product cost of the company. The cost analysis issued by the company, compared to the real cost obtained through this work, showed some distortions and this was considered, either, higher or lower, in many items, as well as the suppression of others. It is possible to determine that the seed production activity is profitable for the company.